Implementation Strategies for Interventions Aiming to Increase Participation in Mail-Out Bowel Cancer Screening Programs: A Realist Review - Myers, Larry; Goodwin, Belinda; Ralph, Nicholas; Castro, Oscar; March, Sonja (Frontiers in Oncology, 2020)
Background: Bowel cancer is the third most commonly diagnosed cancer and the third most common cause of cancer-related death with 1,849,518 new cases of bowel diagnosed, and 880,792 deaths reported globally in 2018 alone. Survival can be improved through early detection via national mail-out bowel cancer screening programs; however, participation remains low in many countries. Behavior change is therefore required to increase participation. This realist review aims to (a) identify the behavior change techniques (BCTs) used in each intervention, (b) understand the mechanisms of action responsible for the BCTs effectiveness, and (c) apply a behavior change model to inform how behavior change techniques and mechanisms of action (MoA) can be combined to increase screening participation. Methods: We systematically reviewed the literature for interventions aiming to increase participation in mail-out bowel cancer screening. We used a four-stage realist synthesis approach whereby; (1) interventions were extracted from each study; (2) BCTs applied in each intervention were identified and coded using the BCT taxonomy-v1; (3) the Theory and Techniques tool was used to link BCT to their mechanisms of action; and (4) BCT and MoA were categorized according to their effectiveness and what Health Action Process Approach (HAPA) stage of change they would affect. Results: We identified 68 intervention trials using 26 unique BCTs and 13 MoA to increase participation. Sixteen BCTs and 10 MoA were identified within the interventions that successfully increased participation rates. Interventions targeting both stages of the HAPA model had a higher success rate (80%) than those targeting one stage of change (51%). When targeting only one stage, interventions targeting the volitional stage had a higher success rate (71%) than interventions only targeting the motivational stage of change (26%). Conclusion: Importantly, this review identified a suite of BCTs and MoA that are effective for increasing participation in mail-out bowel cancer screening programs. With increased participation in bowel cancer screening leading to improved survival, our findings are key to informing the improvement of policy and interventions that aim to increase screening using specific strategies at key stages of health decision-making.